Penegakan Hukum Pidana dalam Perlindungan Hewan di Indonesia (International Forum of Researchers and Lecturers, 2025)
Enforcement of criminal law in animal protection in Indonesia is increasingly becoming an important concern in line with increasing public awareness regarding animal rights. Even though Indonesia has a number of laws and regulations that regulate the protection of animals, such as Law no. 18 of 2009 concerning Animal Husbandry and Animal Health, in reality violations of animal rights still often occur, both in the form of physical violence and animal exploitation. This research aims to examine the extent to which criminal law in Indonesia can provide effective protection for animals, as well as the obstacles faced in its implementation. The focus of this research includes analysis of existing legal regulations, including Law no. 41 of 2014 concerning Forestry, as well as an evaluation of the effectiveness of criminal law enforcement in tackling acts of violence against animals. The research method used is a qualitative approach with literature studies and legal analysis to dig deeper into how legal protection for animals is implemented in practice, as well as the obstacles faced by law enforcement officials. It is hoped that this research will provide insight into the importance of stricter and more effective law enforcement, as well as provide recommendations for improving animal protection through policy adjustments and increasing public awareness.